A bisimidazolium-based cationic covalent triazine framework for CO2 capture and dye adsorption. (5th December 2021) - Xi, Sun-Chang; Guo, Hao-Nan; Yang, Chang-Yuan; Wang, Ren; Wang, Dong-Yue; Dong, Bin
Graphical abstract: A bisimidazolium-based cationic covalent triazine framework behaved as an efficient adsorbent for both CO2 capture and dye removal. Highlights: A bisimidazolium cationic covalent triazine framework (PyImCl-cCTF) was synthesized. PyImCl-cCTF exhibited high CO2 uptake superior to the previously reported cCTFs. PyImCl-cCTF showed a certain versatility for removal of anionic and cationic dyes. PyImCl-cCTF exhibited fast kinetics towards anionic dyes. Abstract: In this work, an aromatic nitrile containing the pyrimidine moiety and bisimidazolium cations (PyImCl) was synthesized and subsequently employed to prepare a bisimidazolium-based cationic covalent triazine framework (PyImCl-cCTF) through the ionothermal trimerization reaction. The chemical composition and structure of PyImCl-cCTF were carefully revealed by a series of techniques. As examined by N2 sorption isotherms at 77 K, PyImCl-cCTF exhibited large surface area and abundant microporous structures. Together with the high content of imidazolium cations derived from the bisimidazolium-based monomer, PyImCl-cCTF showed high CO2 uptake capacity of 235 and 133 mg/g at 1 bar under 273 and 298 K, respectively, superior to the previously reported cCTFs. The dye adsorption performance of PyImCl-cCTF was performed for commonly used dyes. Surprisingly, PyImCl-cCTF exhibited a certain removal effect on both anionic and cationic dyes. Moreover, PyImCl-cCTF with the positively charged skeleton can quickly remove anionic dyes through electrostatic interactions, showing almost 100% removal efficiency within 20 min. These results demonstrate that PyImCl-cCTF can behave as an efficient adsorbent for both CO2 capture and dye removal to solve environmental problems.